Pengaruh Tqm, Sistem Pengendalian Internal, Sistem Penghargaan Dan Sistem Pengukuran Kinerja Terhadap Kinerja Manajerial - Wahyuni Nengsi, Neni Sri (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This study aims to determine the effect of TQM, Internal Control System, Reward System, Performance Measurement System on Managerial Performance. With a sample of 124 respondents obtained by the slovin formula in the population of employees who are registered at the Public Works Office of Solok Regency. The sampling technique is accidental sampling. The analytical method used is multiple linear regression and using SPSS.The results obtained based on the Partial Test (t test) obtained TQM, Internal Control System, Reward System, Performance Measurement System have a positive and significant effect on Managerial Performance. The results of the study based on the Simultaneous Test (F-Test) of TQM, Internal Control System, Reward System, Performance Measurement System together have a significant effect on Managerial Performance. With the contribution of service quality, implementation of tax audits and modernization of the tax administration system on personal taxpayer compliance, it is 83.2% while 16.8% is influenced by other variables that are not examined in this study.